1986
DOI: 10.1128/mcb.6.10.3373
|View full text |Cite
|
Sign up to set email alerts
|

Transient inhibition of DNA synthesis results in increased dihydrofolate reductase synthesis and subsequent increased DNA content per cell.

Abstract: We examined the role that blockage of cells in the cell cycle may play in the stimulation of gene amplification and enhancement of drug resistance. We found that several different inhibitors of DNA synthesis, which were each able to block cells at the G1-S-phase boundary, induced an enhanced cycloheximide-sensitive synthesis of an early S-phase cell cycle-regulated enzyme, dihydrofolate reductase, and of other proteins as well. This response was specific, in that blockage at the G2 phase did not result in over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Cycloheximide inhibits DNA synthesis in tion to the degree of protein synthesis inh (32 (16). Based in part on this observation, it has been proposed that the accumulation of proteins occurring during S-phase block with HU is important for facilitating the emergence of MTX-resistant cells during subsequent selection (16,28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cycloheximide inhibits DNA synthesis in tion to the degree of protein synthesis inh (32 (16). Based in part on this observation, it has been proposed that the accumulation of proteins occurring during S-phase block with HU is important for facilitating the emergence of MTX-resistant cells during subsequent selection (16,28).…”
Section: Discussionmentioning
confidence: 99%
“…While the mechanism of this effect is not understood, dihydrofolate reductase (DHFR) and several other unidentified proteins accumulate during the cell cycle block induced by HU and aphidicolin (APC) (16). These proteins have been proposed to include proteins involved in DNA synthesis which contribute after release of the cell cycle block to the overreplication of DNA and facilitate the development of MTX resistance (16,28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The antifolate agent, methotrexate, is an analog of dihydrofolate that binds specifically to DHFR and inhibits its enzyme activity. Treatment of cells with methotrexate results in elevated levels of DHFR (90,91) that are paralleled by an incrase in DHFR mRNA (92). The 5'-flanking region of the human (93), murine (94) , and hamster (9 5) DHFR genes exhibit a high degree of sequence conservation .…”
Section: Eukaryotesmentioning
confidence: 99%
“…We reported previously that carcinogens induce gene amplification and enhanced gene expression of simian virus 40 (SV40) and dihydrofolate reductase (17, 19, 20, 20a). Metabolic inhibitors of DNA replication induce similar effects (15,36). Recently, we have shown that enhanced expression of two unlinked genes occurs in the same subpopulation of treated cells, suggesting the involvement of trans-acting cellular factors in this process (Kleinberger et al, submitted for publication).…”
mentioning
confidence: 95%